Identifikasi Patologi Birokrasi Guna Mewujudkan Good Governance Di Kantor Kelurahan Pemerintah Kota Kediri - Bambang Dwi Handoyo; Arisyahidin Arisyahidin; Ahsin Daroini (Universitas Islam Kadiri, 2022)
A good bureaucracy has the capacity to understand and fulfill the public’s need. The resistor factor for efforts to create a good bureaucracy is there is presence of a disease in the body of the bureaucracy called bureaucratic pathology. Ngronggo Village as a bureaucratic unit that provides public services is required to work professionally and be able to quickly respond to aspirations, public demands and environmental changes, but in reality it doesn’t work properly. The purpose of this research is to determine how to identify bureaucratic pathology, types of bureaucratic pathology, factors that impact the emergence of bureaucratic pathology, and efforts to resolve bureaucratic pathology in order to realize good governance in the Kediri City Government Village Office.This research was qualitative research. The data collection methods used were interviews, observation and documentation. The data analysis method used were data reduction, data presentation and conclusion.The results of this research in Ngronggo Village showed that based on the identification of bureaucratic pathological behavior there was deviant behavior carried out by village employees. The implementation of services in general had been going well. The types of bureaucratic pathology in Ngronggo Village besides being undisciplined, there were negative behaviors such as, they didn’t have concern for the workload and employee motivation was still low and it maight work productivity was low too. The factors that impact this came from income, environment, and the non-applicability of employee disciplinary regulations. With the role of leaders who made efforts to overcome bureaucratic pathological behavior.This research concluded that in Ngronggo Village there is bureaucratic pathological behavior. So it is necessary to apply the concept of good governance which is a solution to minimize bureaucratic disease by running the government openly (transparency), good control, and accountability for government performance.